Comparative analysis of the returns to education in Germany and Hungary (2000) - Szilvia Hámori (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2005)
In this study standard Mincer earnings equations are estimated using both ordinary least squares (OLS) and quantile regression in order to give a comprehensive picture of the returns to education in Germany and Hungary for the year 2000. To make the cross-country comparison of the returns to education informative, six differentiated categories for formal education, rather than years of schooling, are generated and used in the empirical analysis. Moreover, the returns to three and eight field of study groups for Germany and Hungary respectively are estimated in order to shed more light on the valuation of specific university degree. Most importantly, the empirical results provide evidence for the fact that the OLS estimate is not an accurate estimate of the return to education for the population (more specifically for the selected samples). That is, the estimates of the quantile regressions point to the fact that differences in returns to education within educational groups contribute significantly to aggregate earnings inequality, especially in Hungary.
Keywords: C13; I21; J24; J31; 330; Quantile regression; education systems; return to education; between-educational-levels earnings inequality; within-educational-levels earnings inequality; Bildungswesen; Bildungsertrag; Vergleich; Schätzung; Deutschland; Ungarn